Evaluation of Gravity and Altimetry Data in Australian Coastal Regions - Claessens, Sten (Springer, 2012)
Satellite altimetry in near-coastal marine areas is notoriously problematic, and gravity anomalies derived from various satellite-altimetry-derived gravity models differ significantly near the coast. In this paper, gravity anomalies from the DNSC08 and Sandwell & Smith v18.1 (SS18) models are compared and ‘validated’ against shipborne and airborne gravity anomalies around the Australian coast. Due to the scarcity of high-quality gravity observations just off the coast, a true validation of the models cannot be achieved. However, DNSC08 conforms slightly better to both shipborne and airborne gravity observations closest to the coast in selected test areas, although the standard deviation of differences between the models and the test data barely exceeds the estimated test data accuracy.